How strange: Coenosia curiosa sp. nov. (Diptera: Muscidae), the first recorded Tiger fly from Lesotho, with revision of the Coenosia globuliseta-group - Muller, Burgert S.; Midgley, John M. (Zootaxa, 2022)
A new species of tiger fly, Coenosia curiosa sp. nov., is described from the Kingdom of Lesotho. It is also the first record of the genus for Lesotho. An identification key is provided for the C. globuliseta-group, which now includes four species with aberrant males that have enlarged apically globular frontal setae, thus far known only from southern Africa. Diagnoses, material examined and terminalia illustrations for all known species of the C. globuliseta-group are also provided.